Hipercium species in the treatment of depression - a literature overview - Drożdżał, Justyna; Barańska, Oliwia; Chańko, Małgorzta; Krzaczkowski, Adam; Niedzielska, Emilia; Rędaszka, Magadalena; Szuba, Joanna; Szular, Zofia; Wojczulis, Tymon; Ziemek, Katarzyna (Quality in Sport, 2025)
Hypericum perforatum, commonly known as St. John’s wort, has gained considerable attention as a herbal alternative in the treatment of mild to moderate depression. Given its favorable safety profile, natural origin, and evidence-based efficacy, it may represent a valuable support tool in mental health care, including among physically active individuals. The plant’s therapeutic potential stems from the synergistic action of compounds such as hyperforin and hypericin, which modulate neurotransmitter systems and neuroinflammation. Clinical studies and meta-analyses confirm that H. perforatum demonstrates comparable effectiveness to conventional antidepressants, while showing fewer side effects. Although its interaction with other medications requires caution, the growing interest in phytotherapy highlights its relevance in supporting psychological well-being, especially in stress-prone populations, such as athletes or individuals seeking non-pharmacological interventions.